Effect of Safety Culture, Safety Leadership, and Safety Climate on Employee Commitments and Employee Performance PT. Pelindo III (Persero) East Java Province - Benny Agus Setiono; Ida Ayu Brahmasari; Siti Mujanah (Universitas Sebelas Maret, 2018)
This study aims to analyze the effects of safety culture, safety leadership and the safety climate on organizational commitment and employee performance. Using the survey method, responses from 218 respondents were collected to understand the complete picture of a port service industry in Indonesia. Data were analyzed with Structural Equation Model (SEM) and it reveals that each safety culture variable, safety climate safety leadership, and employee commitment has a positive and significant impact on employee performance. Organizational commitment variables may enhance the effects of safety culture, safety leadership and a safety climate on employee performance.